Persepsi Industri Kota Batam terhadap Super Tax Deduction - Arniati; Dedi Kurniawan; Rizki Lanniari HS; Afriyanti Hasanah; Anjelina (Directorate General of Taxes, 2025)
The super tax deduction provision enables the industrial sector to engage in vocational education initiatives by innovating and enhancing human resources to cultivate a better, more competent workforce. Nonetheless, the actual circumstances do not align with the anticipated objectives. Consequently, this investigation was undertaken. This research seeks to examine the attitude of Batam City's industry about the super tax deductions law and the use of tax incentives in industrial operations. The investigator used a descriptive qualitative methodology with a purposive sample strategy. The analytical method was used to handle raw data derived from the distribution of questionnaires and focus group discussions (FGD) involving 13 industries in Batam City. The research findings suggest that the use of the super tax deductions tax facility in Batam City's industry remains suboptimal. This results from insufficient government support for socialization and help with the super tax deductions rule. The government must strengthen the super tax deduction socialization strategy to prevent uneven regulations. Furthermore, the government must provide explicit directives on the methodologies for computing and reporting super tax deduction facilities. The government may use the findings of this research to assess implemented policies. Taxpayers may use it as supplementary information for tax preparation via tax incentives.